Answer:
![g(x) = |x - 3|](https://tex.z-dn.net/?f=g%28x%29%20%20%3D%20%7Cx%20-%203%7C)
Step-by-step explanation:
Given
![f(x) = |x|](https://tex.z-dn.net/?f=f%28x%29%20%3D%20%7Cx%7C)
Required
Translate 3 units right
The result of a right translated function is:
![g(x) = f(x - h)](https://tex.z-dn.net/?f=g%28x%29%20%3D%20f%28x%20-%20h%29)
<em>Where h is the unit of translation</em>
<em></em>
<em></em>
<em></em>
<em></em>
<em></em>
Solve for f(x - 3)
![f(x) = |x|](https://tex.z-dn.net/?f=f%28x%29%20%3D%20%7Cx%7C)
![f(x - 3) = |x - 3|](https://tex.z-dn.net/?f=f%28x%20-%203%29%20%3D%20%7Cx%20-%203%7C)
Hence;
![g(x) = |x - 3|](https://tex.z-dn.net/?f=g%28x%29%20%20%3D%20%7Cx%20-%203%7C)
Answer:
so whats the question
Step-by-step explanation:
F(x)+g(x) = (x+7) + (x-3) =
x + 7 + x - 3 =
2x + 4
<span>
A.2x+4</span>
Answer: it’s acute
Step-by-step explanation:
Answer:The approximate square root is 2.23
Step-by-step explanation:√ 5 = 2.23
Thus: 2.23 x 2.23 = 5